Thinking Process of Student in Solving Mathematical Problems Based on Logis-Mathematical Intelligence - Purjiyo Purjiyo; Imam Sujadi; Diari Indriati (BIRCU, 2022)
The root of the problem of this research is the lack of interest in student learning during the COVID-19 pandemic which resulted in low student learning outcomes. The purpose of this study was to see the improvement of student learning outcomes during online learning by using learning videos on a two-variable linear equation system material. The type of research used in this research is classroom action research which was carried out at MTS Negeri 1 Simalungun. This research was conducted in two cycles with each action including planning, implementing, observing and reflecting. To see the learning outcomes used tests in cycles I and II. The results of the study show that learning video media on the material of a two-variable linear equation system in the Covid-19 Pandemic Era can improve learning outcomes and minimum learning mastery of students in class VIII-5 MTS Negeri 1 Simalungun for the 2020/2021 academic year